2011
DOI: 10.1097/pec.0b013e31820d6460
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of Two Systems of Classification for the Diagnosis of Acute Appendicitis

Abstract: Both scores are a useful tool in the evaluation of children with possible AA. For extreme values of scores, the results really ensure their use in the emergency department. The AUS can help on decision making for intermediate values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 20 publications
5
83
0
3
Order By: Relevance
“…[7][8][9][10][11][12] The sensitivity, specificity, and diagnostic accuracy of the Alvarado score were reported to be between 84.2-92%, 66.7-91.2%, and 87-92%, respectively. [30][31][32][33] The sensitivity, specificity, and diagnostic accuracy of the Lintula score in adults are reported to be 87%, 98%, and 91%, respectively. [14] All three articles found through a PubMed-based literature research on the Lintula scoring system are written by Lintula et al [7,14,34] According to the results of the present study, the diagnostic accuracy of the Alvarado and Lintula scoring systems in our patients was consistent with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The sensitivity, specificity, and diagnostic accuracy of the Alvarado score were reported to be between 84.2-92%, 66.7-91.2%, and 87-92%, respectively. [30][31][32][33] The sensitivity, specificity, and diagnostic accuracy of the Lintula score in adults are reported to be 87%, 98%, and 91%, respectively. [14] All three articles found through a PubMed-based literature research on the Lintula scoring system are written by Lintula et al [7,14,34] According to the results of the present study, the diagnostic accuracy of the Alvarado and Lintula scoring systems in our patients was consistent with the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kulik et al 16 examined the performance of six unique clinical decision rules in 4,200 children with suspected appendicitis. The authors concluded that although the PAS and the Alvarado scores were the best validated, 16,[18][19][20][21] neither score met the current performance benchmarks. With respect to the key diagnostic strategies, Ramarajan et al 11 conducted a retrospective review of an appendicitis pathway where children with equivocal initial US underwent clinical examinations and those with persistent abdominal pain had CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…The PAS quantifies the probability of appendicitis by using clinical data (anorexia, vomiting, migration of pain, right lower quadrant tenderness, pain with hopping/coughing, and fever) and laboratory data (white blood cell count > 10 9 10 9 cells/ L, neutrophil count >7.5 9 10 9 /L). 13 This instrument was created specifically for children, 13 has previously been demonstrated to have good interobserver reliability when using consistent measurements, 20 has been prospectively validated in multiple settings, [18][19][20][21] and thus represents the best validated appendicitis-related instrument. 16 However, since a high-quality, consistently high-performing clinical prediction rule for appendicitis has not been identified to date, 16 we have limited the use of the PAS as an entry criterion, and all management decisions were made without its use.…”
Section: Study Setting and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfred Bond [6], Escriba [7], Dado [8] consider the performance of the score as being very good, while others like Macklin [9], Hsiao [10[, Schneider [11] consider the results as being modest.…”
Section: Discussionmentioning
confidence: 99%